Synergistic effects of potassium and gibberellin on the yield and quality of yellow pitahaya (Hylocereus megalanthus) fruits in the Peruvian Amazon - Santos-Pelaez, Julio Cesar; Leiva-Espinoza, Santos Triunfo; Espinoza-Núñez, Erick; Saravia-Navarro, David; Castillo-Torrejon, Carlos Luis; Cruz-Delgado, Julio H. I.; Klauer-Garcia, Dieter Fritz; Melgar, David Pavel Casanova Nuñez (Frontiers in Agronomy, 2025)
The cultivation of yellow pitahaya (Hylocereus megalanthus) is increasing in tropical regions due to its nutritional value and market potential. Yet, agronomic strategies integrating nutrient and hormonal regulation remain scarcely studied. This research evaluated the combined effect of potassium (K2O) and gibberellic acid (GA3) on yield and fruit quality in field-grown pitahaya in the Peruvian Amazon using a 4 × 2 factorial randomized block design with four potassium doses (0, 50, 100, 150 kg ha⁻¹) and two GA3 levels (0 and 50 mg L⁻¹). The combination of 100 kg K2O ha⁻¹ and 50 mg L⁻¹ GA3 significantly improved fruit performance, with fruit weight (369.5 g), yield (12 t ha⁻¹), volume (322 cm³), and soluble solids (22.8°Brix), while acidity decreased (pH 4.87 vs. 4.55 in the control). Potassium alone had a limited impact on fruit weight per plant, but under GA3 application, a quadratic response was evident, with maximum values between 100–110 kg K ha⁻¹. Multivariate analyses confirmed that yield gains were driven by increases in fruit size and quality, with fertilized treatments clearly separated from controls. These findings demonstrate a synergistic interaction between potassium and GA3, providing a basis for precision fertilization protocols that enhance yield and quality in high-value tropical fruit systems.